Advanced thyristor-based cycloconverter for efficient three-phase conversion with low THD - Mahbubur Rahman Tahmid; Md. Abdul Malek; Md. Rafiul Islam; Muhammad Abdul Goffar Khan (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
The growing demand for sustainable systems capable of serving three-phase loads from a single-phase grid has spurred significant research. Conventional DC-link-based single-phase to three-phase converters and variable frequency drives require massive and expensive processing units. Additionally, they have a high conduction loss as they involve multiple conversion stages. Similarly, traditional single-phase to three-phase cycloconverters suffer from excessive harmonic distortion in the output voltage and current. This article proposes a new single-phase to three-phase cycloconverter to reduce harmonics of the output voltage. This design employs a Specially-tapped Single-phase Transformer (STSPT), in which the secondary side of the transformer has 4 extra taps to create multiple voltage levels of sinusoidal pulses. These taps are placed according to calculations and simulations, which enabling frequency and phase conversion using only a single conversion stage with a reduced THD. Detailed analysis is presented, including its response to variable output frequency settings such as 16.67 Hz, 12.5 Hz, 10 Hz, and 8.33 Hz with resistive and motor loads. Multiple voltage levels of sinusoidal pulses in the output signal theoretically reduce the THD by up to 20% compared to conventional designs. A prototype of the cycloconverter was developed and the experimental results confirm close agreement with the theoretical predictions, demonstrating a THD reduction of up to 19% in the output voltage and current compared to conventional models, which makes it a reliable system to drive three-phase loads from a single-phase supply.